Analysis of Factors Affecting Work Productivity of Implementing Nurses at Mataram University Hospital - Ezar Hadiyan; Sastrawan Sastrawan; Sismulyanto Sismulyanto; Saimi Saimi; Sulaiman Sulaiman; Lalu Abdul Khalik; Anak Agung Ayu Niti Wedayani (Jurnal Penelitian Pendidikan IPA, 2025)
Nurses' work productivity plays a crucial role in determining the quality of healthcare services in hospitals. Various factors, including job satisfaction, rewards, competence, job stress, and work environment, are believed to influence nurse productivity. This study aims to identify the dominant factors influencing nurse productivity at Unram Hospital. The purpose of this study was to identify factors that influence nurses' work productivity at Unram Hospital and determine which factors most significantly affect their productivity. This research method used a quantitative approach with a cross-sectional design. Data analysis using descriptive statistical analysis was carried out using a frequency distribution table, while bivariate analysis was conducted using the chi-square test, with Fisher's Exact Test used as an alternative when necessary. Multivariate analysis was conducted using multiple linear regression to assess the influence of each factor on nurse work productivity. The results of the study showed a significant relationship between job satisfaction (p = 0.000), rewards (p = 0.004), and competence (p = 0.001) with work productivity. However, job stress (p = 0.448) and work environment (p = 0.193) did not show a significant relationship. Multivariate regression analysis showed that job satisfaction (β=140.491, p=0.001) was the dominant factor influencing nurses' work productivity, followed by rewards (β=10.084, p=0.076). Job satisfaction emerged as the dominant factor influencing nurses' work productivity at Unram Hospital. Therefore, hospitals should prioritize improving job satisfaction to improve the quality of healthcare services provided